Analisis Budaya Organisasi Menggunakan Organizational Culture Assessment Instrument (OCAI) pada PT. X - Bella Fanya; Annisa Lestari Kadiyono; Rezeki Ashriyana (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
Organizational culture is the main component of a company in making functional decisions and differentiates it from competing companies in order to compete competitively to achieve company success. The purpose of this research is to find out a description of current and future culture at PT. X. There are 4 organizational cultures according to OCAI, namely Clan, Adhrocracy, Market, and Hierarchy. This research uses descriptive research with a quantitative approach. The sampling technique used accidental sampling and got 30 respondents. The results showed that the type of Clan culture that dominates today and is the desired culture in the future. The results of this study can be used as input for PT. X to improve organizational culture to better support organizational effectiveness.